Pengaruh Motivasi Belajar dan Minat Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XI IPS SMA Negeri 1 Sukasada - Tasar, Wilybrodus Beato; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to analyze the influence of learning motivation and interest on the learning outcomes of economics of class XI IPS students at SMA Negeri 1 Sukasada. This study involved all XI IPS students totaling 38 population. The sample used a saturated sampling method considering the limited population. Data collection, namely documentation and questionnaires, was then analyzed using descriptive and multiple linear regression, classical assumption tests and t-tests and F-tests assisted by SPSS. The results are: (1) learning motivation influences learning outcomes; (2) interest influences learning outcomes; (3) learning motivation and interest simultaneously influence learning outcomes. Overall, learning motivation and interest contributed 88,9% to learning outcomes, while the rest was influenced by other factors, namely 11,1%.